The Implementation of Student Teams' Achievement Divisions Applying Multimedia to Improve Learning Outcomes for Fifth Grade Students at Elementary School - Ngatman, Ngatman; Salimi, Moh; Lintang, Niken Sekar; Hidayah, Ratna; Zainnuri, Hasan (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2024)
The study aims to determine the improvement of social science learning outcomes about national events during the colonial period. This study used participatory action research methods conducted in three cycles. The stages were planning, implementing, observing, evaluating, and reflecting. The subjects were teachers and 23 fifth-grade students at an elementary school in the Kebumen district. The data collection methods were observation, interviews, and tests. Data analysis techniques used quantitative and descriptive qualitative analysis. The results indicate that implementing Student Teams Achievement Divisions (STAD) applying multimedia improves student social science learning outcomes since it obtains 73.91% in the first cycle, 80.43% in the second cycle, and 86.96% in the third cycle. The students are active in group discussions and question and answer. It concludes that implementing Student Teams Achievement Divisions by applying multimedia improves social science learning outcomes about national events during the colonial period for fifth-grade students. This study is a diversification of learning strategies, so it can be an alternative solution to develop the quality of learning in elementary schools.